Right‐hand polarized 4fce auroral roar emissions: 2. Nonlinear generation theory. Issue 8 (13th August 2016) - Yoon, P. H.; LaBelle, J.; Weatherwax, A. T.
Abstract: Auroral roar emissions are commonly interpreted as Z (or upper hybrid) mode naturally excited by precipitating auroral electrons. Subsequent conversion to escaping radiation makes it possible for these emissions to be detected on the ground. Most emissions are detected as having left‐hand ( L ) circular (or ordinary O ) polarization, but the companion paper presents a systematic experimental study on the rare occurrence of the right‐hand polarized, or equivalently, extraordinary ( X ) mode 4 f c e emission. A similar observation was reported earlier by Sato et al. (2015). The suggested emission mechanism is the nonlinear coalescence of two upper hybrid roars at 2 f c e . The present paper formulates a detailed theory for such an emission mechanism. Key Points: Nonlinear theory for 4 f ce roar is proposed Two upper hybrid or Z modes merge to emit X mode radiation Theory explains observed 4 f ce roars